Micro-elimination of hepatitis C in people who use injectable drugs along the USA-Mexico border: a modelling study - Lara K Marquez, PhD; Clara Fleiz, PhD; Carlos Magis-Rodriguez, ProfPhD; Natasha K Martin, ProfDPhil (Elsevier, 2022)
Background: The prevalence of hepatitis C in people who use injectable drugs along the USA-Mexico border is very high (>90%). In 2019, the Mexican government committed to providing hepatitis C treatment with priority for people who use injectable drugs, people living with HIV, and people living in prison or jail, yet the immediate plan for prioritized treatment allocation and rollout remained unclear prior to the COVID-19 pandemic. Understanding which prevention and intervention strategies and at what level of scale-up can achieve the WHO goal of 80% incidence reduction by 2030 along the border is needed. Methods: We adapted our previously published dynamic, deterministic model of hepatitis C transmission among people who use injectable drugs to determine the direct-acting antiviral treatment allocations in combination with harm-reduction interventions (opiate agonist therapy and needle and syringe programmes) needed to achieve the WHO elimination goal between 2021 and 2030. Our model is calibrated and parameterised to epidemiological data from Ciudad Juarez (where approximately 10 000 people who use injectable drugs reside and the seroprevalence of hepatitis C among people who use injectable drugs is 92%) and minimal harm reduction. Findings: To reduce hepatitis C incidence by 80% between 2021 and 2030, 910 direct-acting antiviral treatments per 10 000 people who use injectable drugs in Ciudad Juarez per year are needed. Overall, fewer treatments are required if combined with harm reduction. If opiate agonist therapy and needle and syringe programmes are scaled-up to 50%, approximately 30-40% fewer people who use injectable drugs would need to be treated each year (650 direct-acting antiviral treatments per 10 000 people who use injectable drugs per year). Between 2021 and 2030, using direct-acting antivirals alone, an estimated total of 8190 people who use injectable drugs in Ciudad Juarez would need to be treated, compared with 6255 (nearly 25%) fewer people who use injectable drugs overall if treatment is scaled-up alongside 50% of opiate agonist therapy and needle and syringe programmes combination intervention coverage. Interpretation: Hepatitis C treatment with direct-acting antivirals should be prioritised for people who use injectable drugs along the USA-Mexico border and progress towards hepatitis C elimination should be monitored. Regional hepatitis C micro-elimination among people who use injectable drugs could be possible if national treatment allocations are prioritised and distributed to people who use injectable drugs as planned and in the presence of essential harm-reduction programmes. Funding: National Institutes of Health; Fogarty International Center grant D43TW009343; and National Institute of Allergy and Infectious Diseases and National Institute on Drug Abuse grant R01AI147490.